Porn Masturbation Orgasm (PMO) dengan Kecerdasan Kognitif Pada Remaja - Ishariani, Linda; Taukhid, Muhammad; Susmiatin, Eko Arik (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Masturbation is a deviant behavior carried out by teenagers. Porn masturbation orgasm (PMO) behavior can have an impact on reducing brain performance so that it can affect teenagers' cognitive intelligence. The purpose of this research is analyze the corerelation between porn masturbation orgasm and cognitive intelligence in adolescents. The research design used in this correlation with a cross sectional approach. A population of 117 teenagers was obtained from a sample of 39 respondents using purposive sampling technique. The independent variable in this research is porn masturbation orgasm and the dependent variable is cognitive intelligence. The measuring tools are the PMO questionnaire and the C1-C6 cognitive intelligence questionnaire. The test used in this research is Spearman Rho. The results of this study show that the majority (82.8%) carry out masturbation behavior in the moderate category and the majority (71.8%) have the moderate cognitive intelligence category with a P value of 0.009 <α= 0.05, meaning there is a strong correlation between PMO with cognitive intelligence. The correlation coefficient is negative, or the relationship is not in the same direction, meaning that the heavier the value of PMO behavior, the lower the cognitive intelligence value of adolescents. This happens because PMO behavior can damage the brain in the pre-frontal cortex. PFC experiences damage due to being flooded with dopamine so that it changes shape, which can disrupt the function of cognitive intelligence. It is recommended that teenagers increase their productivity to avoid masturbatory behavior that dominates teenagers' productive time, so as not to trigger addiction to masturbation and inhibit the process of cognitive intelligence